Evaluation of atomic oxygen catalytic coefficient of ZrB2–SiC by laser-induced fluorescence up to 1473 K. (11th June 2018) - Meng, Songhe; Zeng, Qingxuan; Jin, Hua; Wang, Liuwei; Xu, Chenghai
Abstract: The atomic oxygen catalytic coefficient, as a key parameter for evaluating the catalytic heat contribution of thermal protection materials, requires thorough and principled experimental studies. In this study, a laboratory-based catalytic coefficient evaluation method based on laser-induced fluorescence diagnosis in radiofrequency inductively coupled plasma and mole fraction gradient theory was investigated. Using this method, the atomic oxygen catalytic coefficients were determined for water-cooled copper, quartz of different temperatures, and, for the first time to our knowledge, ZrB2 –SiC ceramics up to 1473 K. The validity of the proposed method is compared with the results from published studies using optical emission spectroscopy and laser-induced fluorescence methods.